(untitled) - Silvia R. D. T. de Siqueira; Mariana Siviero; Fábio K. Alvarez; Manoel J. Teixeira; José T. T. de Siqueira (Arquivos de Neuro-Psiquiatria)
The objective of this article was to investigate, with a systematic protocol of quantitative sensory testing, patients with persistent idiopathic facial pain (PIFP) and others with trigeminal traumatic neuropathic pain (TTN) compared to controls. Thirty patients with PIFP, 19 with TTN, and 30 controls were evaluated on subjective numbness and dysesthesia and with a systematic protocol of quantitative sensory testing for thermal evaluation (cold and warm), mechanical detection (touch and pinpricks for mechanical pain), superficial pain thresholds, and corneal reflex. We found that PIFP and TTN had numbness and dysesthesia higher than controls (p<0.001 and p=0.003), and that in both of them mechanical pain by pinpricks detection was abnormal intra and extra orally at the mandibular branch (p<0.001). Cold, warm, and tactile detections and pain thresholds were similar among the groups. Corneal reflex was abnormal in TTN (p=0.005). This study supports neuropathic mechanisms involving pain processing in PIFP and that the criterion on absence of sensorial variations in PIFP should be revised. O objetivo deste artigo foi investigar, com um protocolo sistemático de testes sensitivos quantitativos, pacientes com dor facial idiopática persistente (DFIP) e outros com dor neuropática trigeminal traumática (DNTT) comparado aos controles. Trinta pacientes com DFIP, 19 com DNTT e 30 controles foram avaliados quanto à dormência e à disestesia subjetiva e por meio de um protocolo sistemático de testes sensitivos quantitativos, que incluiu avaliação térmica (frio e quente), detecção mecânica (táctil e alfinetes), limites de dor superficial e reflexo córneo-palpebral. Foi observado que os pacientes apresentaram mais dormência e disestesia do que os controles (p<0,001 e p=0,003), além de mais anormalidades intra e extraorais no ramo mandibular (p<0,001). As alterações de calor, frio, dor e tato foram semelhantes entre os grupos. O reflexo córneo-palpebral foi anormal somente no grupo com DNTT (p=0,005). Este estudo suporta mecanismos de dor neuropática envolvidos no processamento da DFIP, e o critério de ausência de variações sensoriais nesta deve ser revisto.